A mulher e a casa: Estudo sobre a relação entre as transformações da arquitetura residencial e a evolução do papel feminino na sociedade carioca no final do século XIX e início do século XX - Patricia Thome Junqueira (2012)
The Brazilian house is a topic that has been studied and analyzed by historians and architects for some time. Several approaches are possible, from the construction technique to architecture, including the symbolic values of living space and its cultural and social meanings. This research studies the house based on a social vision, looking into the relationship between the domestic space and the woman. The woman chosen as research subject belongs to the highest class, because she is the most reclusive among all social levels and therefore possibly had a greater influence on the spatial layout of the residences. The study object is the homes of the privileged sectors of Rio de Janeiro´s society of the late nineteenth and early twentieth century. They are instituted as a means to understanding the society that was being built, mainly to define the importance of women's role within this high class republican society and their contribution to the development of the concept of living in Brazil. The main objective is to draw a parallel between the changes occurring in the social structure in Rio de Janeiro, focusing on the social role of women, and the changes in the form of living, in the distribution of spaces and appearance of homes. After this woman belonging to the carioca elite is found, transformed in " home queen" by literature, religion, politics and science, in the bourgeois houses of the fin de siècle in Rio de Janeiro, and investigate their influence on the design of domestic spaces and the concept of living, it becomes possible to identify the points that reinforce the hypothesis presented that the woman should be considered a transforming agent of residential space.